Thin‐Film Composite Membrane with a Hydrophobic Substrate for Robust Membrane Distillation. Issue 7 (24th January 2023) - Xie, Shaodan; Chen, Yuanmiaoliang; Feng, Dejun; Wang, Zhangxin
Abstract: Membrane distillation (MD) is a promising thermal desalination technology, but its application is largely limited by membrane wetting. This study introduces a thin‐film composite (TFC) membrane comprising a polyamide (PA) surface layer, a polydopamine (PDA) interlayer, and a hydrophobic polyvinylidene fluoride (PVDF) membrane substrate for anti‐wetting MD operations. With a PDA reaction time of 1 h, a compact and hydrophilic PDA interlayer forms on the PVDF membrane substrate, facilitating the subsequent formation of the PA surface layer. With 2 cycles of interfacial polymerization process, a dense PA surface layer forms on the PDA interlayer, rendering a TFC membrane with robust wetting resistance. From diffusion experiments and breakthrough pressure measurements, the TFC membrane exhibits excellent wetting resistance because the dense PA surface layer can prevent the wetting contaminants from reaching the hydrophobic membrane substrate due to the combination of the size exclusion effect and capillary effect. The results from this study shed lights on a new approach for the fabrication of robust MD membranes for practical applications. Abstract : In this study, a thin‐film‐composite (TFC) membrane comprising a dense polyamide surface layer, a hydrophilic polydopamine interlayer, and a hydrophobic polyvinylidene fluoride membrane substrate for robust anti‐wetting MD operations are fabricated. Due to the size exclusion effect and capillary effect, the as‐fabricated TFC membrane exhibits excellent wetting resistance in MD operations.